Orthodontic treatment need from a bibliometric analysis of the last four decades: a bibliometric analysis - Yusra, Yohana; Kusnoto, Joko; Gunardi, Indrayadi; Goalbertus, Goalbertus; Kusnoto, Budi (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Malocclusion is a common oral disorder that strongly correlates with orthodontic treatment needs (OTN), however the complete picture of OTN remains unclear. This bibliometric study was conducted to develop a complete picture of the OTN from 1974-2022. The purpose of this study was to conduct a bibliometric analysis of scientific research pertaining to orthodontic treatment needs Methods: Type of study was bibliometric analysis. The term